Enhancement of Medical Students' Performance and Motivation in Pathophysiology Courses: Shifting From Traditional Instruction to Blended Learning - Dan Wang; Junhai Zhou; Qiuhui Wu; Guannan Sheng; Xin Li; Huiling Lu; Jing Tian (Frontiers Media S.A., 2022)
Blended learning is a learning approach that combines face-to-face classroom lectures and e-learning. It has grown rapidly to be commonly used in medical institutions, especially in the local medical universities where there is lack of qualified teachers and instructional materials. Massive open online courses (MOOCs) are the latest revolution in e-learning and provides learners with access to quality educational resources. Nevertheless, there is seldom reports concerning how to effectively integrate MOOCs into blended learning in local universities, as well as the evaluation of knowledge outcomes. In order to achieve this aim, a blended learning approach was carried out in teaching pathophysiology in Guilin Medical University. This blended learning model was based on combination of Chinese University MOOC with case based learning (CBL), as an alternative to conventional learning. The medical students in the 2017 and 2018 classes received the blended learning method, while the medical students in the 2015 class received the traditional classroom instruction. The results showed that students in the 2017 and 2018 performed significantly better than students in the 2015 class at mid-term exam and the final exam. Perception surveys also revealed that both students and teachers had positive attitude toward blended learning, and they shared similar viewpoints of blended learning. A large proportion of students and teachers believed that the blended learning enhanced students' motivation to learn independently, improved their time management skills, and allowed them to experience personalized learning. Also, most students and teachers recognized that Chinese University MOOC provided substantial educational resources suitable for their need. In addition, teachers indicated that the blended learning improved student learning quality, facilitated interaction between teachers and students, and helped them to establish a student-centered model in teaching pathophysiology. Overall, the blended learning method that combines Chinese University MOOC with CBL is effective in enhancing students' achievement and motivation in pathophysiology than the traditional learning method, and helps to strengthen the cultivation of talent in local medical universities.